Two-way shape memory effect and its degradation during thermal cycles in Ni-Ti alloys - Scherngell, Heinrich (Kovine zlitine tehnologije, 1997)
This work presents a study of the degradation of the Two-Way Shape Memory Effect (TWSME) due to working cycles. An intrinsic TWSME was induced in wire specimens of a near equiatomic Ni-Ti alloy by thermomechanical training. The development of the two way strain was analysed and discussed with respect to the different training parameters and the preliminary heat treatment of the samples. Subsequent to the training, the stability of the obtained TWSME was examined by thermal cycling under stress-free conditions. Possible reasons and mechanisms for the degradation of the effect during thermal cycling are discussed.
Keywords: titan; zlitine; nikelj; stabilnost; natezni preizkus; vpliv temperature; utrujenost materialov